KETERAMPILAN MENGGUNAKAN KOMPUTER DALAM MATA PELAJARAN TIK PADA PESERTA DIDIK KELAS V DI SD BINA NUSA - Anjani, Siti Ratna; Hakim, Zerri Rahman; Rakhman, Patra Aghtiar (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to describe students’ skills in using computers and identify supporting and inhibiting factors in the implementation of Information and Communication Technology (ICT) learning at SD Bina Nusa, Tangerang Regency. The research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. Data analysis followed the stages of data collection, data reduction, data display, and conclusion drawing. The validity of the data was ensured through credibility tests, including prolonged engagement, triangulation, peer discussion, transferability, dependability, and confirmability. The findings showed that fifth-grade students already possessed basic computer skills, such as operating hardware, managing files, and using Microsoft PowerPoint in learning activities. Supporting factors for ICT learning included the availability of a computer laboratory, teacher support, and students’ motivation. Meanwhile, the main challenges were limited instructional time, differences in students’ abilities, and technical issues with computer devices. In conclusion, ICT learning at SD Bina Nusa has been implemented effectively and contributes to improving elementary students’ digital skills.